A new 3D model for genotoxicity assessment: EpiSkin™ Micronucleus Assay. (18th February 2020) - Chen, Lizao; Li, Nan; Liu, Yanfeng; Faquet, Brigitte; Alépée, Nathalie; Ding, Chunmei; Eilstein, Joan; Zhong, Lingyan; Peng, Zhengang; Ma, Jie; Cai, Zhenzi; Ouedraogo, Gladys
Abstract: The European Regulation on Cosmetics (no. 1223/2009) has prohibited the use of animals in safety testing since March 2009 for ingredients used in cosmetics. Irreversible events at the chromosome level (clastogenesis and aneugenesis) are commonly evaluated by scoring either micronuclei or chromosome aberrations using cell-based genotoxicity assays. Like most in vitro genotoxicity assays, the 2D in vitro micronucleus assay exhibits a poor specificity and does not mimic the dermal route. To address these limitations, the current project aims to develop and validate a 3D micronucleus assay using the EpiSkin™ model. This project is scientifically supported by the Cosmetics Europe Genotoxicity Task Force. In a first step, two key criteria for the development of micronucleus assay, namely, the sufficient yield of cells from the EpiSkin™ model and an acceptable proliferation rate of the basal layer, were assessed and demonstrated. Subsequently, six chemicals (vinblastine, n -ethylnitrosourea, β-butyrolactone, 2-acetylaminofluorene, 2, 4-dichlorophenoland d -limonene) were evaluated in the EpiSkin™ Micronucleus Assay. At least two independent experiments using 48- and 72-h incubations were performed for each chemical. Results showed good inter-experimental reproducibility, as well as the correct identification of all six tested chemicals. The metabolism of 2-acetylaminofluorene on the EpiSkin™ model was also investigated and confirmed by the formation of an intermediate metabolite (2-aminofluorene). These preliminary results from the EpiSkin™ Micronucleus Assay indicate that it is a promising in vitro assay for assessing genotoxicity. The availability and suitability of this test method contribute significantly to the development of non-animal testing methods in China and its impact on the worldwide field.